THE EFFECT OF TEACHERS’ CREATIVITY ON STUDENTS INTEREST IN LEARNING ENGLISH IN THE SECOND GRADE SMP NEGERI 2 TINAMBUNG - Hestika; Nur Qalbi; Farisha Andi Baso (Journal of Language Testing and Assessment, 2021)
This research is aimd to find out the effect of teachers’ creativity The Effect of Teachers’ Creativity on Students Interest in Learning English in The Second Grade SMP Negeri 2 Tinambung. The problem statements are two namely: 1) How is students perception of learning English?, What are the effect of teachers’ creativity on students’ interest in learning English at SMP Negeri 2 Tinambung ?.This research was descriptive qualitative. The population is the second grade student SMP Negeri 2 Tinambung which consist of 25 students. The sample taken from B class of SMP Negeri 2 Tinambung. The instrument use are interview and questionnaire. However, the subjects of this research were 25 students of the second grade at SMP Negeri 2 Tinambung. The researcher employed Descriptive-qualitative method and the instrument of this research were conducted through interview and questionnaire The research findings showed that the effect of teachers’ creativity on student’s interest in learning English was very important it can increase student enthusiasm for receiving the material and can increased students interest in learning English.